Utility of Rapid Antibody Test for Screening COVID-19 Among Healthcare Professionals - Okay, Gulay; Kacmaz, Asiye Bahar; SÜMBÜL, BİLGE; Sumbul, BİLGE; Bolukcu, Sibel; OKAY, GÜLAY; DURDU, BÜLENT; Akkoyunlu, Yasemin; Durdu, Bulent; AKKOYUNLU, YASEMİN; Meric Koc, Meliha (My University, 2020)
Objective: This study aims to assess the effectivity of a rapid antibody test on detecting the occupational exposure in healthcare professionals who have been working in a pandemic hospital since the initial cases were seen in our country.